TINGKAT MOTIVASI TERHADAP KOMITMEN KARYAWAN PADA PT. KALTIM PRIMA COAL (KPC) KALIMANTAN TIMUR (Studi Pada Bidang Penanganan Air, Lumpur dan Penambangan) - Muhammad Akbar (ADMINISTRASI PUBLIK, 2018)
East Kutai Regency is a region with high population and distribution, the government uses a letter of introduction as an invitation or mediator to carry out socialization to the community. And beyond that, the civil service and civil registry also cooperate with other parties, for example, providers who provide network development for the management of SIAK and public and private organizations that require population data.Information System of Population Administration (SIAK) is a government policy that is set in order to improve the quality of government services, especially in the field of population administration. Population administration information has a strategic value for the administration, development and service to the community, so that the need for the management of population administration information in a coordinated and sustainable manner. To ensure the accountability of services to the public in a single-point reservation, it is necessary to establish policies and information systems for population administration nationally.Population Administration is a series of activities of structuring and controlling in the issuance of documents and Population Data through Population Registration, Civil Registration, Information Management of Population Administration and utilization of the results for public services and other sectors development.Population registration Is recording of population biodata, recording of population event report and population data collection Vulnerable population administration and control of population documents in the form of identity card or certificate of residence. Population is Everyone both Indonesian citizens and foreign nationals residing in the territory of the Republic of Indonesia and has complied with the provisions of the applicable Laws and Regulations.People who have KTP are Indonesian citizens and Foreigners who have Permanent Stay Permit and have been 17 (seventeen) years old or have been married or have been married legally.The family is a person or group of people who have blood relations and / or other people who live in one house / building and registered in the Family Card. The Family Card is a family identity card containing data on names, family arrangements and relationships, and family identity.